Maternal high-fat diet promotes calcified atherosclerotic plaque formation in adult offspring by enhancing transformation of VSMCs to osteochondrocytic-like phenotype. Issue 9 (September 2022) - Miyawaki, Daisuke; Yamada, Hiroyuki; Saburi, Makoto; Wada, Naotoshi; Motoyama, Shinichiro; Sugimoto, Takeshi; Kubota, Hiroshi; Wakana, Noriyuki; Kami, Daisuke; Ogata, Takehiro; Matoba, Satoaki
Abstract: Aim: Maternal high-fat diet (HFD) is associated with the development of cardiovascular disease (CVD) in adult offspring. Atherosclerotic vascular calcification is well documented in patients with CVD. We examined the effect of maternal HFD on calcified plaque formation. Methods and results: Seven-week-old female apo-E −/− mice (C57BL6/J) were nourished either an HFD or a normal diet (ND) a week before mating, and during gestation and lactation. Offspring of both the groups were fed a high-cholesterol diet (HCD) from 8 weeks of age. Osteogenic activity of the thoracic aorta, assessed using an ex vivo imaging system, was significantly increased after 3 months of HCD in male offspring of HFD-fed dams (O-HFD) as compared with those of ND-fed dams (O-ND). Alizarin-red-positive area in the aortic root was significantly increased after 6 months of HCD in male O-HFD as compared to that of O-ND. Plaque size and Oil Red O-positive staining were comparable between the two groups. Primary cultured vascular smooth muscle cells (VSMCs) of the thoracic aorta were treated with phosphate and interleukinL-1β (IL-1β) to transform them into an osteochondrocytic-like phenotype. Intracellular calcium content and alkaline phosphatase activity were markedly higher in the VSMCs of O-HFD than in O-ND. IL-1β concentration in the supernatant of bone marrow-derived macrophages was markedly higher in O-HFD than in O-ND. Conclusion: Our findings indicate that maternal HFD accelerates the expansion of atherogenic calcification independent of plaque progression. In vitro phosphate- and IL-1β-induced osteochondrocytic transformation of VSMCs was augmented in O-HFD. Inhibition of VSMCs, skewing toward osteochondrocytic-like cells, might be a potential therapeutic strategy for preventing maternal HFD-associated CVD development. Abstract : Maternal high-fat diet; Atherosclerosis; Cardiovascular calcification; Interleukin-1β.